Annual Body Mass Index Gain and Risk of Gestational Diabetes Mellitus in a Subsequent Pregnancy - Tano, Sho; Kotani, Tomomi; Ushida, Takafumi; Yoshihara, Masato; Imai, Kenji; Nakano-Kobayashi, Tomoko; Moriyama, Yoshinori; Iitani, Yukako; Kinoshita, Fumie; Yoshida, Shigeru; Yamashita, Mamoru; Kishigami, Yasuyuki; et al. (Frontiers in Endocrinology, 2022)
Introduction Weight change during the interpregnancy is related to gestational diabetes mellitus (GDM) in the subsequent pregnancy. In interpregnancy care/counseling, the timeframe for goal setting is important, while the timing of the next conception is unpredictable and preventing age-related body weight gain is difficult. This study aimed to investigate the association between annual weight gain during the interpregnancy, which provide clearer timeframe, and GDM in subsequent pregnancies. Methods This multicenter retrospective study was conducted by collecting data on two pregnancies of the same women in 2009–2019. The association between annual BMI gain and GDM during the subsequent pregnancy was examined. Results This study included 1,640 pregnant women. A history of GDM (adjusted odds ratio [aOR], 26.22; 95% confidence interval [CI], 14.93–46.07) and annual BMI gain (aOR, 1.48; 95% CI, 1.22–1.81) were related to GDM during the subsequent pregnancy. In the women with a pre-pregnant BMI of <25.0 kg/m2 and without GDM during the index pregnancy, an annual BMI gain of ≥0.6 kg/m2/year during the interpregnancy were associated with GDM in subsequent pregnancies; however, in the other subgroups, it was not associated with GDM in subsequent pregnancies. Conclusions For women with a pre-pregnant BMI of <25.0 kg/m2 and without GDM during the index pregnancy, maintaining an annual BMI gain of <0.6 kg/m2/year may prevent GDM during the subsequent pregnancy.